Participatory negotiation in decision-making of hmong ethnic people: The Nam Ngiep 1 hydropower plant project, Lao PDR - Sypha Chanthavong (2018)
© 2017, Greater Mekong Subregion Academic and Research Network, Asian Institute of Technology. The Lao government emphasizes hydropower development as a priority as the economic benefits from hydropower development are very significant for the Lao economy. However, the hydropower decision-making process is a complex business, involving different layers and requiring multiple participants, influencing both society and the environment. Understanding the hydropower decision-making processes, in particular the participation of the Hmong ethnic in these negotiations has important implications. This paper will scrutinize how participatory negotiation practices affect the Hmong ethnic people in the decision-making process of the Nam Ngiep 1 Hydropower Project. Simultaneously, the question of how the Hmong ethnic people negotiate with powerful actors like the state and the project developer to protect their rights and benefits requires an answer. The results of the study find that Hmong affected by the Nam Ngiep 1 Hydropower Project use many negotiation tactics in order to protect their rights and benefits, such as identity, network, and historical memory. Moreover, Hmong also use oral and written negotiation forms to protect their rights and benefits.